How breastfeeding affects immunity? - Piecuch, Dawid; Sobota, Weronika; Zemsta, Katarzyna; Piskorz, Przemysław; Zwoliński, Michał; Hańczyk, Edyta; Sędek, Aleksandra (Quality in Sport, 2025)
Introduction and objective A person's health is influenced by various factors, one of which is diet, which can be altered to provide many needed ingredients. The early years of life are crucial for building immunity, starting with breast milk as the primary food. Breastfeeding offers unique benefits, including providing maternal antibodies, immunoglobulins and growth factors that lower the risk of many diseases. In the work presented here, we focus mainly on the components of maternal milk and the benefits of providing them. Review methods PubMed/MEDLINE databases were searched using the entry criteria “full text” and the exclusion criteria “systematic reviews,” “meta-analyses” and “review articles.” The phrases “breastfeeding,” “immunity” and “breast milk composition” were included. In the end, 40 publications were left out. Abbreviated description of the state of knowledge This study describes the main components of breast milk that build a baby's immunity. The mechanisms of action of these components are key to understanding how food can affect long-term human health and immunity, especially that provided in the first days of life. Summary Breastfeeding affects the development and functioning of the baby's operating system. Due to the special composition of breast milk, breastfed children protect against infections and support for additional health. Mechanisms that cause side effects that cause effects not only in the aftermath of life, but also in the aftermath of health in the aftermath of life.